PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN KONSUMEN PADA DEALER YAMAHA GRAHA BATAM - Arianto, Isidorus Joko; Heryenzus (SCIENTIA JOURNAL, 2021)
Business development has grown rapidly, giving rise to various significant competitions, especially in the automotive sector. The purpose of this study was to determine the effect of service quality and facilities on customer satisfaction at Yamaha Graha Dealers in Batam City partially and simultaneously. Samples of consumers who came to Yamaha Graha Batam Dealers were 182 respondents. The sampling method used was accidental sampling and the data collection technique used a questionnaire (questionnaire). The results of this study are known t-test where the results of the t-test for service quality 4.580> t table 1.653 significant value 0.000 <0.05 and for facilities 8.236> 1.653, significant value 0.000 <0.05. Based on the results of the study, it can be concluded that service quality partially has a positive and significant effect on customer satisfaction (H1 is accepted) and facilities partially also has a positive and significant effect on consumer satisfaction (H2 is accepted). The results of the f test where f count 98,870 > f table 3.04 and a significant value of 0.000 <0.05. The results can be concluded that the quality of service and facilities simultaneously has a positive and significant effect on customer satisfaction (H3 is accepted).